Galectin‐1 ameliorates perioperative neurocognitive disorders in aged mice. (4th May 2021) - Shen, Zhiwen; Xu, Hui; Song, Wen; Hu, Chuwen; Guo, Mingyan; Li, Jinfeng; Li, Junhua
Abstract: Introduction: The incidence of perioperative neurocognitive disorders (PND) is higher in the elderly patients undergoing surgery. Microglia activation‐mediated neuroinflammation is one of the hallmarks of PND. Galectin‐1 has been identified as a pivotal modulator in the central nervous system (CNS), while the role of galectin‐1 in PND induced by microglia‐mediated neuroinflammation is still undetermined. Methods: An exploratory laparotomy model anesthetized with isoflurane was employed to investigate the role of galectin‐1 on PND in aged mice. Open field test and Morris water maze were used to test the cognitive function 3‐ or 7‐days post‐surgery. The activation of microglia in the hippocampus of aged mice was tested by immunohistochemistry. Western blot, enzyme‐linked immunosorbent assay (ELISA), and quantitative real‐time polymerase chain reaction (qRT‐PCR) were employed to elucidate the underlying mechanisms. Results: Galectin‐1 attenuated the cognitive dysfunction induced by surgery in aged mice and inhibited microglial activity. Moreover, galectin‐1 decreased the expression level of inflammatory proteins (interleukin‐1β, interleukin‐6, and tumor necrosis factor‐α), and prevented neuronal loss in the hippocampus. Galectin‐1 inhibited the inflammation of BV2 microglial cells induced by lipopolysaccharide via decreasing the translocation of NF‐κB p65 and c‐Jun, while this kind of inhibition was rescued when overexpressing IRAK1. Conclusion: Our findings provide evidence that galectin‐1 may inhibit IRAK1 expression, thus suppressing inflammatory response, inhibiting neuroinflammation, and improving ensuing cognitive dysfunction. Collectively, these findings unveil that galectin‐1 may elicit protective effects on surgery‐induced neuroinflammation and neurocognitive disorders. Abstract : Galectin‐1 ameliorated hippocampus‐dependent cognitive dysfunction induced by surgery. Furthermore, galectin‐1 mitigated surgery‐induce systemic inflammation and neuroinflammation induced by surgery through attenuating the transcriptional activity and translocation of c‐Jun and NF‐κB p65.